PERANAN BAZNAS DALAM MENCIPTAKAN MASYARAKAT PRODUKTIF UNTUK MENGENTASKAN KEMISKINAN DI KABUPATEN PADANG PARIAMAN - DOLA NOFELINA; FERY ANDRIANUS; ZULKIFLI ZULKIFLI (Maqdis: Jurnal Kajian Ekonomi Islam, 2020)
This study aims to see and analyze the role of BAZNAS in creating productive communities to alleviate poverty in Padang Pariaman Regency. This study uses primary data. The method used in this research is descriptive analysis with SEM (Structural Equation Modeling) approach with PLS (Partial Least Square) technique. The sample used in this study were 39 mustahiq in Kabupaten Padang Pariaman who received venture capital assistance from BAZNAS. The results of the research conducted, it was found that the variable of venture capital assistance had a positive and significant effect on community business productivity and the variables of business assistance and community business productivity had a positive and significant effect on the poverty alleviation variable.